Perancangan Sistem Transaksi Laundry Berbasis Website Menggunakan Metode Extreme Programming Studi Kasus (CV. Mutiara Ilham) - Gunawan Atmaja; Ilham Jaya Firmansyah; Opik Hidayat Abdul Latif; Saprudin (CV. Shofanah Media Berkah, 2023)
Rapid developments in information and communication technology and the need for efficient services have driven businesses to adopt computerized solutions. CV. Mutiara Ilham, a laundry business, faces challenges in manually recording transactions and financial reports. To overcome this problem, a web-based laundry application was designed to improve the performance of Melati Laundry. It is hoped that the use of this system will improve service quality, reduce the risk of data loss, and speed up reporting. However, the implementation of this system requires careful attention to all related aspects.